Tonic Effects Test of Pegagan (Centella asiatica L.) Syrups on White Male Mice - Sunarti, Sunarti; Keswara, Yane Dila; Purnamasari, Nuraini Dewi (Jurnal Farmasi Indonesia, 2016)
Centella asiatica L., or known as pegagan leaf, empirically can be used as a tonic for organs such as liver, kidneys and brain. It also can increase memory. In our society, Centella asiatica L., hasnâ??t been optimally processed as atonic. Commonly, it is processed by boiling or grating the leaf. Raw consumption of this leaf inflicts bad taste. The aim of this research is to find out tonic effect and determine the effective dose of herbal syrup Centella asiatica L. The effect of tonic can be determined using natatory exhaustion method, by observing stimulant effect of a certain drug to an animal.Methods : This research used male mice were divided into 5 groups of treatment. The first group: negative control without herbal syrup Centella asiatica L., substance, positive control 50 mg/kg body weight, first dose group 120 mg/kg miceâ??s body weight, second dose group 150 mg/kg miceâ??s body weight and third dose group 180 mg/kg miceâ??s body weight. The effect of tonic was observed through the increasing duration of the miceâ??s self-defense ability when it was swum.Result: This research resulted that the use of herbal syrup Centella asiatica L., gave tonic effect on dose 120 mg/kg miceâ??s body weight, 150 mg/kg miceâ??s body weight, and 180 mg/kg miceâ??s body weight. The most effective dose of the use of herbal syrup Centella asiatica L., is on dose 180 mg/kg miceâ??s body weight.